2017
DOI: 10.1007/s12186-017-9181-z
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Adult Learning Research Field by Analysing Who Cites Whom

Abstract: In this article we report on findings from a large-scale bibliographic study conducted based on the citation practices within the field of research on adult learning. Our data consist of 151,261 citation links between more than 33,000 different authors whose papers were published in five leading international journals in the field of adult learning during the time period 2006-2014. By analysing the composition of the dominating citation clusters we are able to construct a telescopic view of the research field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Our CBL approach is thoroughly anchored in theories of lifelong inclusive learning, as essential ingredients for HEIs' commitment and contribution to societal transformation. We argue that the role of HEIs is also to advance adult lifelong learning towards a sustainable global learning society (Nylander et al, 2018). However, to make this successful, we realise the importance of integrating theories of change into adult learning concepts in HE (Kezar, 2014).…”
Section: Concluding Arguments and Challengesmentioning
confidence: 99%
“…Our CBL approach is thoroughly anchored in theories of lifelong inclusive learning, as essential ingredients for HEIs' commitment and contribution to societal transformation. We argue that the role of HEIs is also to advance adult lifelong learning towards a sustainable global learning society (Nylander et al, 2018). However, to make this successful, we realise the importance of integrating theories of change into adult learning concepts in HE (Kezar, 2014).…”
Section: Concluding Arguments and Challengesmentioning
confidence: 99%
“…Hieronymus et al [14] have reported the influence of four factors incentivizing adult education program namely; requirement to seek democracy deliberately, significance of vital communities, efficacy of groups and enabling mature adults [14]. It aims in inculcating the responsible behaviour in terms of group leader and group participator in any community group or program working towards a better society [14][15][16]. The classifications of state and local organizations role in proliferating adult education programs lies in establishment of strong adult education leadership in the state departments of education, consultancy services, dissemination, research and financial access by state organizations and restricted to specific community for local organizations, respectively [14][15][16].…”
Section: Platforms Required For Adult Education and Lifelong Learning...mentioning
confidence: 99%
“…It aims in inculcating the responsible behaviour in terms of group leader and group participator in any community group or program working towards a better society [14][15][16]. The classifications of state and local organizations role in proliferating adult education programs lies in establishment of strong adult education leadership in the state departments of education, consultancy services, dissemination, research and financial access by state organizations and restricted to specific community for local organizations, respectively [14][15][16]. Midtsundstad et al [10] has reviewed the impact of formal adult learning programs on employment sector and labour market participation and have found strong correlation of the basic skills imparted to them with their output efficacy.…”
Section: Platforms Required For Adult Education and Lifelong Learning...mentioning
confidence: 99%
“…In an ongoing research project on the bibliometrics of adult education research (Fejes andNylander, 2014, 2015;Fejes and Nylander, 2018;Nylander et al, 2017), we have conducted such analyses of adult education journals. Firstly, we engaged in an analysis of who is publishing in three of the more 'central' journals in the adult education research field, and secondly we focused on who in these journals are picked up and cited (see Fejes and Nylander, 2014 for an elaboration on the topic).…”
Section: Changing Behaviour Among Educational Researchersmentioning
confidence: 99%
“…In a more recent study (Nylander et al, 2017), we explore, in greater detail, the dominant players within this research field. Based on a database of all citations in the reference lists of all articles in five journals in the adult-learning field during 2006-2014, altogether amounting to more than 33,000 authors and 151,000 citation links, we outline the bibliographies and field positions of the most cited scholars.…”
Section: Changing Behaviour Among Educational Researchersmentioning
confidence: 99%